Long‐Term Outcome of Patients with Bifascicular Block and Unexplained Syncope Following Cardiac Pacing. Issue 10 (22nd September 2016) - KALSCHEUR, MATTHEW M.; DONATEO, PAOLO; WENZKE, KEVIN E.; ASTE, MILENA; ODDONE, DANIELE; SOLANO, ALBERTO; MAGGI, ROBERTO; CROCI, FRANCESCO; PAGE, RICHARD L.; BRIGNOLE, MICHELE; HAMDAN, MOHAMED H.
Abstract : Background: According to the ACC/AHA/HRS guidelines, cardiac pacing is reasonable in patients with bifascicular block (BF‐B) and syncope when other causes have been excluded. The purpose of this study was to assess the long‐term outcome of patients with BF‐B and unexplained syncope following cardiac pacing. Methods and Results: Between 2009 and 2015, we identified 43 consecutive patients (mean age of 78 ± 12 years, 64% males) who presented with syncope and BF‐B and had received a pacemaker (PM). During a mean follow‐up period of 31 ± 21 months, syncope recurred in seven patients (16%): 7% (95% standard error [SE] ± 3%) at 1 year and 18% (95% SE ± 7%) at 5 years. At univariable analysis, the only predictor of syncope recurrence was empiric pacing (P = 0.03). There were no syncope recurrences in the 12 patients who received a PM following a positive electrophysiological study (EPS) and the five patients with documentation of paroxysmal atrioventricular block (AVB) during cardiac monitoring (insertable loop recorder [ILR]), (EPS/ILR Group, n = 17) compared to seven of 26 (27%) patients who received empiric pacing (Empiric Group, n = 26; P = 0.02). Progression to high‐degree AVB was documented during follow‐up in 16 (37%) patients: nine of 17 (53%) patients in the EPS/ILR Group and seven of 26 (27%) patients in the Empiric Group (P = 0.11). There were no injuries reported during ILR monitoring. Conclusions: We have shown that syncope recurs not infrequently in patients with BF‐B who received pacing for syncope. Nearly one in four patients who had empiric pacing suffered syncope recurrence compared to no recurrences in patients who received a PM following a positive EPS or documentation of transient AVB.